Ellipsis and its Application in Dramatic Speech - Andaniyazova Gavkhar Ruzikulovna (Research Parks Publishers, 2022)
As every researcher works on a novel, aimes to make his/her novel read by people, certainly tries to pay attention to making attractive the speech of its heroes and tries to describe his/ her emotion. Speech of heroes gives the opportunity of using all grammar means of the language skillfully, choosing and creating newer and newer expessions in order to strengthen the esthetic impact. In the novels by Sharof Boshbekov one of the language means was skillfully utilized by ellipsis to express the fluency, influence and naturalistic speech of heroes.